2016
DOI: 10.1155/2016/3086036
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection as a Possible Cause of Spontaneous Abortion and Spontaneous Preterm Delivery

Abstract: Based on the current literature, we aimed to provide an overview on Human Papillomavirus prevalence in normal pregnancies and pregnancies with adverse outcome. We conducted a systematic literature search in PubMed and Embase. Data extracted from the articles and used for analysis included HPV prevalence, pregnancy outcome, geographical location, investigated tissue types, and HPV detection methods. The overall HPV prevalence in normal full-term pregnancies was found to be 17.5% (95% CI; 17.3–17.7) for cervix, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 83 publications
(123 reference statements)
3
76
1
3
Order By: Relevance
“…In placental and aborted tissues, the infection rate was slightly lower, with a summary estimate of 8.3% (95% CI 7.6–9.1). Correspondingly, the prevalence of HPV was significantly higher in the cervix and placental and aborted tissue of women who underwent spontaneous abortions [7]. Although the prevalence of HPV was significantly different in normal pregnancies and the spontaneous abortion group, our results based on 5 cohort studies and 3 case-control studies indicated that there was no significant association between HPV infection and spontaneous abortion (OR 1.40; 95% CI 0.56–3.50).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In placental and aborted tissues, the infection rate was slightly lower, with a summary estimate of 8.3% (95% CI 7.6–9.1). Correspondingly, the prevalence of HPV was significantly higher in the cervix and placental and aborted tissue of women who underwent spontaneous abortions [7]. Although the prevalence of HPV was significantly different in normal pregnancies and the spontaneous abortion group, our results based on 5 cohort studies and 3 case-control studies indicated that there was no significant association between HPV infection and spontaneous abortion (OR 1.40; 95% CI 0.56–3.50).…”
Section: Discussionmentioning
confidence: 71%
“…In normal full-term pregnancy, prevalence of HPV was reported to vary between 2.2 and 75% in the cervical tissue, with a summary estimate of 17.5% [7]. In placental and aborted tissues, the infection rate was slightly lower, with a summary estimate of 8.3% (95% CI 7.6–9.1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, HPV can be transmitted vertically from the mother to the child during delivery which may result in neonatal and congenital, oral, or conjunctival lesions. 18,19 Anogenital warts in immunsupression: Immuncompromised individuals have a higher risk of malignant transformation and higher risk of coinfection with more than one HPV type and also have a higher viral load. AGWs are larger and more treatment resistant with higher recurrence rates.…”
Section: Special Conditionsmentioning
confidence: 99%
“…Our logic would also imply a role for (potentially male-derived) microbes in miscarriages and spontaneous abortions. A microbial component to these seems well established for both miscarriages [481][482][483] and spontaneous abortions [484][485][486][487][488][489]. Of course the ability of Brucella abortus to induce abortions in domesticated livestock, especially cattle (and occasionally in humans), is well known [490][491][492]; indeed, bacteriospermia is inimical to fertilisation success [493], and nowadays it is well controlled in livestock by the use of vaccines [494] or antimicrobials [493].…”
Section: Microbial Infections In Spontaneous Abortions Miscarriages mentioning
confidence: 99%